Are Confident Designers Good Teammates to Artificial Intelligence?: A Study of Self-Confidence, Competence, and Collaborative Performance. (May 2022) - Chong, L.; Kotovsky, K.; Cagan, J.
Abstract: For successful human-artificial intelligence (AI) collaboration in design, human designers must properly use AI input. Some factors affecting that use are designers' self-confidence and competence and those variables' impact on reliance on AI. This work studies how designers' self-confidence before and during teamwork and overall competence are associated with their performance as teammates, measured by AI reliance and overall team score. Results show that designers' self-confidence and competence have very different impacts on their collaborative performance depending on the accuracy of AI.